Compassionate presence sessions: A qualitative exploration of experiences of older adults and college students - Angela U. Ekwonye (Aging and Health Research, 2022)
Background: Offering compassionate presence has been associated with enhanced psychological and physiological well-being for both the giver and the recipient, especially in times of crisis, but there are limited studies examining the role of an intergenerational compassionate presence program on the well-being of older and younger adults. This phenomenological study aimed to explore the impact of compassionate presence sessions for older adults and college students during the COVID-19 pandemic. Methods: Data were gathered from older adult participants through semi-structured interviews (n = 18) and student participants through weekly debriefing and structured guided reflection (n = 7). Results: The study identified the intergenerational compassionate presence program as a possible tool for use in strengthening intergenerational bonds, promoting mutual learning, boosting the emotional well-being of older and younger adults, reducing ageist views, enhancing social virtues, and improving college students’ attitudes toward aging and older adults. Conclusion: Findings support the need to implement programs that provide a space for older adults to share their life stories and experiences without being judged. Such an opportunity can help them dig deeper into their inner resources to discover and find meaning in their life experiences.